2018
DOI: 10.1257/pol.20170012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Education on Adolescents’ Intertemporal Choices

Abstract: We study the impact of financial education on intertemporal choice in adolescence. The educational program was randomly assigned among high school students, and choices were measured using an incentivized experiment. Students who participated in the program make more time-consistent choices; are more likely to allocate payments to a single payment date, as opposed to spreading payment across two dates; and display increased consistency of choice with the law of demand. These findings suggest that financial edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 59 publications
6
59
1
4
Order By: Relevance
“…Despite the increasing number of studies that focus on similar issues (e.g., the effect of financial education on financial behavior; for a meta-analysis of experimental studies see [10]), hitherto, a surprisingly small number of studies tackled the described problem either theoretically or empirically. To our knowledge, in the only empirical papers [11][12][13] directly combining income, financial literacy and economic decision-making, the authors found that financial literacy decreases time-discounting although the effects are rather small. Other than that, a recent review [5] presented a hypothesized complex model of a cognitive mechanism describing how can poverty affect economic preferences.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the increasing number of studies that focus on similar issues (e.g., the effect of financial education on financial behavior; for a meta-analysis of experimental studies see [10]), hitherto, a surprisingly small number of studies tackled the described problem either theoretically or empirically. To our knowledge, in the only empirical papers [11][12][13] directly combining income, financial literacy and economic decision-making, the authors found that financial literacy decreases time-discounting although the effects are rather small. Other than that, a recent review [5] presented a hypothesized complex model of a cognitive mechanism describing how can poverty affect economic preferences.…”
Section: Introductionmentioning
confidence: 88%
“…Many programs that aimed to increase financial literacy, and consequently to improve financial behavior had been proposed in the last years. However, the recent evidence [10][11][12]57,60] showed that financial education has only a small effect on financial literacy and almost negligible effect on real-life financial behavior. At the same time, the duration of these effects is very limited, often lasting no longer than one year [57,61].…”
Section: Poverty Economic Preferences and Financial Literacy: What Dmentioning
confidence: 99%
“…In a study conducted in the region of Madrid to assess intervention of financial education programme using data on 22 schools, it was found that the program increased treated students' financial literacy performance between one fourth and one third of a standard deviation (Hospido, Villanueva, & Zamarro, 2015). Luhrmann, Serra-Garcia, and Winter (2014) examined the impact of a financial education intervention on intertemporal choices in adolescence and found that the financial education intervention led to a significant increase in time consistency which could lead to better management of financial plans, less under-saving and over-borrowing.…”
Section: Te Ra Tu R E Re V I Ewmentioning
confidence: 99%
“…With regard to the literature on the causal effects of financial education, Lührmann et al (2018) show that financial education can increase the quality of intertemporal decision-making. Similarly, Berg and Zia (2017) show that an intervention implemented into mainstream-media harnessing emotional connections also impacts financial behavior without necessarily impacting cognitive components of general financial literacy.…”
Section: Potential Mechanisms Of Financial Education Impactmentioning
confidence: 99%